2023
DOI: 10.1039/d2fo03497b
|View full text |Cite
|
Sign up to set email alerts
|

Confusoside, a dihydrochalcone glucoside, prevents acetaminophen-induced liver injury by modulating the Nrf2/NF-κB/caspase signaling pathway

Abstract: Dihydrochalcone compounds are common active ingredients in tea, and the main ingredient of the ethnic herbal tea Anneslea fragrans leaves is a compound confusoside (CF) with a dihydrochalcone structure. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Confusoside (CF) is a dihydrochalcone glucoside found in Anneslea fragrans Wall., a plant belonging to the Theaceae family and Anneslea genus. Widely distributed in southwestern China, this plant contains abundant biologically active molecules such as dihydrochalcone [81] in its leaves. The chemical structure of dihydrochalcone reveals its biological properties, including anti-inflammatory and antioxidant effects, which have significant implications in the prevention and treatment of liver injury [150].…”
Section: Pi3k/akt-related Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Confusoside (CF) is a dihydrochalcone glucoside found in Anneslea fragrans Wall., a plant belonging to the Theaceae family and Anneslea genus. Widely distributed in southwestern China, this plant contains abundant biologically active molecules such as dihydrochalcone [81] in its leaves. The chemical structure of dihydrochalcone reveals its biological properties, including anti-inflammatory and antioxidant effects, which have significant implications in the prevention and treatment of liver injury [150].…”
Section: Pi3k/akt-related Pathwaysmentioning
confidence: 99%
“…The chemical structure of dihydrochalcone reveals its biological properties, including anti-inflammatory and antioxidant effects, which have significant implications in the prevention and treatment of liver injury [150]. CF, a dihydrochalcone glucoside, has been proven to prevent APAP-induced liver injury through three pathways [81]. Firstly, CF can interact with the Keap1-Nrf2 complex, leading to the release of Nrf2 and promoting its translocation into the cell nucleus [151].…”
Section: Pi3k/akt-related Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, natural antioxidants have attracted wide attention from researchers in recent years. Studies have confirmed that several natural antioxidants, such as confusoside, resveratrol, and delphinine have significant antioxidant activities and can effectively induce liver injury by inhibiting oxidative stress (Zhao et al, 2023;De Moraes et al, 2021;Xu et al, 2020). However, the existing types and quantities of natural antioxidants are not enough to meet people's needs.…”
Section: Introductionmentioning
confidence: 99%